2023
DOI: 10.1111/mcn.13511
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors associated with rural‐urban disparities of stunting among under‐five children in Rwanda: A decomposition analysis approach

Abstract: Childhood stunting in its moderate and severe forms is a major global problem and an important indicator of child health. Rwanda has made progress in reducing the prevalence of stunting. However, the burden of stunting and its geographical disparities have precipitated the need to investigate its spatial clusters and attributable factors. Here, we assessed the determinants of under-5 stunting and mapped its prevalence to identify areas where interventions can be directed. Using three combined rounds of the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Some of the environmental factors that may influence these differences include access to healthcare, air pollution, lifestyle, and socio-economics. Studies suggest that differences in access to healthcare and diet may affect health outcomes between urban and rural areas Smith et al, 2019;Fadelu et al, 2022;Samosir, Radjiman & Aninditya, 2023;Kalinda, 2023). In addition, studies highlight the impact of air pollution on public health in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the environmental factors that may influence these differences include access to healthcare, air pollution, lifestyle, and socio-economics. Studies suggest that differences in access to healthcare and diet may affect health outcomes between urban and rural areas Smith et al, 2019;Fadelu et al, 2022;Samosir, Radjiman & Aninditya, 2023;Kalinda, 2023). In addition, studies highlight the impact of air pollution on public health in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Stunting shows a substantial correlation with child age, wealth index, maternal education, and the number of antenatal care visits, according to a Rwandan study on children under the age of five [10]. The same study in Rwanda on children under the age of five found a strong correlation between anemia and parental education level, geographic location, and the child's sex [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of information on the appropriate personal, family, sociocultural, and context-relevant factors. These factors may be bottlenecks in reducing stunting among children under five years, especially in high-risk population areas [ 12 , 14 ]. This qualitative study explored the lived experiences of women and men to identify issues that are key to influencing childhood nutrition and stunting and explore possible solutions to address the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Several national-level analyses have explored the determinants of stunting in Rwanda [ 14 , 15 ]. These studies have provided important insights into the individual, household, and macro drivers of stunting as well as documenting and proposing critical top-down policy directions to enhance stunting reductions.…”
Section: Introductionmentioning
confidence: 99%